Current situation and prospect of coal mine water treatment technology - LI Fuqin; WANG Cong; ZHENG Jiongzhou; CHEN Yuhang; HE Xuwen; DAI Qibin; TIAN Li (Gongye shui chuli)
Coal mine water is an important unconventional water source, and the resource utilization of mine water is of great significance in alleviating water scarcity and environmental protection in mining areas. This paper analyzed the source and water quality characteristics of mine water, and summarized the main treatment technologies of different types of mine water such as suspended solids, high salinity, acidity and special pollutants, as well as the characteristics and existing problems of each treatment technology. The majority of mine water contained a significant amount of suspended solids, with considerable fluctuations in both water quality and quantity. Efforts should be focused on enhancing the presettling capabilities of both underground water storage facilities and surface regulating reservoirs, developing and improving underground treatment technology for mining wells, and combining automation and intelligence to achieve unmanned operation. With the continuous increase of highly salinity mine water, its treatment technology had become a research focus in the field of mine water treatment. It was necessary to strengthen pretreatment, develop efficient technologies to remove silicon and hardness, introduce energy recovery devices, combine new and renewable energy to develop green and energy-saving coupling desalination technology, optimize the zero discharge process as a whole, and reduce the treatment cost of concentrated salt wastewater. Acidity and special pollution were currently the difficulties in mine water treatment, distributed and efficient directional processing technology should be adopted to explore the coupling processes and natural restoration governance. Guided by national policies, mining water treatment technology will develop towards being more energy-saving, highly effective, intelligent, and environmentally friendly.